2017
DOI: 10.1001/jamadermatol.2017.3668
|View full text |Cite
|
Sign up to set email alerts
|

Barber Knowledge and Recommendations Regarding Pseudofolliculitis Barbae and Acne Keloidalis Nuchae in an Urban Setting

Abstract: Pseudofolliculitis barbae (PFB) and acne keloidalis nuchae (AKN) are chronic inflammatory conditions affecting hair follicles common in men of color who are genetically inclined to have tightly curled hair. 1 The incidence of PFB and AKN among African American men may be as high as 83.0% and 13.6%, respectively. 2,3 The barbershop represents a distinctly important institution in the African American community and constitutes a culturally appropriate venue for barbers to provide men with health information. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Previous studies mentioned barber education about pseudofolliculitis barbae and acne keloidalis nuchae. 31 To prevent developing folliculitis, barbers may be informed for diagnosis of folliculitis and disinfection of hair clippers.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies mentioned barber education about pseudofolliculitis barbae and acne keloidalis nuchae. 31 To prevent developing folliculitis, barbers may be informed for diagnosis of folliculitis and disinfection of hair clippers.…”
Section: Discussionmentioning
confidence: 99%
“…1 While studies have examined cardiovascular health, prostate cancer, and diabetes, few have considered the barbershop for expansion of dermatologic care access (eg, salons as clinical sites for skin cancer screening). 2,3 The limited data on dermatologic health disparities suggest that people of color have worse health outcomes and less outpatient care compared with White patients. 4 Certainly, the cause is multifactorial, including access to care.…”
Section: Dermatology In the Black Barbershop: A Potential Opportunitymentioning
confidence: 99%
“…Further, this education could dispel myths and inaccuracies about skin conditions and care perpetuated by media and folklore. For instance, Adotama et al 2 found that although most barbers could correctly identify pseudofolliculitis barbae, their ideas about treatment varied considerably. Consistent, evidence-based education could close knowledge gaps.…”
Section: Dermatology In the Black Barbershop: A Potential Opportunitymentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, papules resolve and leave small zones of alopecia within a field of keloid‐like papules (Figure 1B). 1 While the etiology of AKN is not well established, it is known to be triggered by chronic inflammation or occlusion of follicles due to haircutting practices, trauma, and friction 2,3 . Additionally, systemic factors such as increased sensitivity or excess of androgens, infections, autoimmunity, and insulin resistance may also contribute to the development of AKN 4…”
Section: Introductionmentioning
confidence: 99%